From instruction to delight : an anthology of children's literature to 1850 / edited by Patricia Demers & Gordon Moyles. - Demers, Patricia; Moyles, R. G. (Robert Gordon), 1939- (Oxford University Press, 1982)
An anthology of poetry and prose read by and to children from the Middle Ages to the mid-nineteenth century, including familiar as well as little-known examples from each period